Parathyroid adenoma-An incidental diagnosis - Nandini Chatterjee; Chandan Chatterjee (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2018)
A 50 year old man was referred to us with inadequate control of blood pressure for last few years. He was being treated as a case of essential hypertension on a four drug regime. Subsequent work up led to the diagnosis of primary hyper parathyroidism due to left inferior parathyroid adenoma.